A nudged chemistry‐climate model simulation of chemical constituent distribution at northern high‐latitude stratosphere observed by SMILES and MLS during the 2009/2010 stratospheric sudden warming. Issue 3 (12th February 2016) - Akiyoshi, H.; Nakamura, T.; Miyasaka, T.; Shiotani, M.; Suzuki, M.
Abstract: Stratospheric sudden warming (SSW) is a dramatic phenomenon of the winter stratosphere in which the distribution of chemical constituents, associated chemical tendency, and transport of chemical constituents differ significantly inside and outside of the polar vortex. In this study, the chemical constituent distributions in the major SSW of 2009/2010 were simulated by the Model for Interdisciplinary Research on Climate 3.2‐Chemistry‐Climate Model (CCM) nudged toward the European Center for Medium‐Range Weather Forecasts‐Interim Re‐Analysis data. The results were compared with Superconducting Submillimeter‐Wave Limb‐Emission Sounder (SMILES) and Microwave Limb Sounder (MLS) observations. In addition, ozone tendency due to ozone transport and chemical ozone loss in the high‐latitude lower stratosphere before and after the SSW was analyzed for the period from 1 January 2010 to 11 February 2010. The evolution and distribution of ozone and HCl inside/outside the polar vortex associated with the vortex shift to the midlatitudes in January are quite similar between SMILES and MLS. Those of ClO are also similar, considering the difference in the local time for the measurement. Analyses of the nudged CCM run indicate that inside the polar vortex at 50 hPa, the ozone concentration increased moderately owing to partial cancelation between the large negative ozone tendency due to chemical ozone destruction and large positive ozone tendency due to horizontal ozone influx from outside of the vortex as well as downward advection. In the region of a high ozone concentration with the same area as that of the polar vortex at 50 hPa, the large increase in ozone was primarily due to a downward advection of ozone. SMILES and MLS observations, nudged CCM simulations, and ozone tendency analyses revealed a highly longitudinal dependent ozone tendency at high latitudes during the SSW. Key Points: O3, HCl, and ClO during the 2009/2010 SSW are compared between SMILES and MLS O3, HCl, and ClO from a REF‐C1SD simulation by a nudged CCM are compared with SMILES and MLS O3 tendency inside/outside the Arctic polar vortex during the SSW from the simulation is analyzed